Apremilast survival and reasons for discontinuation in psoriasis: five-year experience from a Greek tertiary care centre - Sotiriou, Elena; Tsentemeidou, Aikaterini; Sideris, Nikolaos; Lallas, Aimilios; Kougkas, Nikolaos; Ioannides, Dimitrios; Vakirlis, Efstratios (Dermatology Practical & Conceptual, 2022)
Introduction: Drug survival is an indirect measure of efficacy and safety and its post-marketing assessment using real-life data is invaluable.Objectives: To investigate the survival of apremilast in a cohort of psoriasis patients treated with apremilast in a Greek hospital.Methods: A retrospective cross-sectional study examined adult psoriasis patients receiving apremilast (March 2016 to January 2021). Primary endpoint was the cumulative survival probability at 52 weeks. Kaplan-Meier analysis was used to calculate survival probability. Cox regression analysis was performed to investigate potential risk factors for apremilast discontinuation.Results: 102 patients (29.4% females) with a mean age of 55.94 years (Standard Deviation 15.21) were included. 65 patients (63.7%) had discontinued treatment by lock date: 19 (18.6%) due to lack of efficacy, 24 (23.5%) due to loss of efficacy, 15 (14.7%) due to adverse reactions, and 7 (6.86%) due to other reasons. Cumulative survival probability at 52 weeks was 52.1%. Median survival time for all reasons for discontinuation was 58 weeks 95%Confidence Interval (40.02, 75.98).Conclusions: Approximately half of patients remained on apremilast after a year of treatment. Secondary drug failure was the most common reason for discontinuation.